2023
DOI: 10.1055/s-0043-1764317
|View full text |Cite|
|
Sign up to set email alerts
|

Examination of Proximodistal Patellar Position in Dogs with the Stifle at Full Extension

Abstract: Objective The aim of this study was to determine the factors related to functional patella alta, with which the proximodistal patellar position exceeds the reference range of healthy small dogs proximally when the stifle is at full extension. Study Design Mediolateral-view radiographs of dogs weighing less than 15 kg were obtained and classified into the medial patellar luxation (MPL) and control groups. The reference range of the proximodistal patellar position was determined from the control group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In canine orthopaedics, ROC analysis has been used to evaluate parameters related to developmental diseases, such as hip dysplasia (Gaspar et al, 2016) and medial elbow coronoid disease (Hersh-Boyle et al, 2021). In dogs with patellar luxation, only the cutoff values of femoral trochlear morphological parameters (Longo et al, 2023) and indices of proximodistal patellar position (Murakami et al, 2023) have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In canine orthopaedics, ROC analysis has been used to evaluate parameters related to developmental diseases, such as hip dysplasia (Gaspar et al, 2016) and medial elbow coronoid disease (Hersh-Boyle et al, 2021). In dogs with patellar luxation, only the cutoff values of femoral trochlear morphological parameters (Longo et al, 2023) and indices of proximodistal patellar position (Murakami et al, 2023) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In human medicine, there are numerous studies on patellofemoral diagnostic imaging parameters, and the use of ROC analysis to outline those that seem most relevant in the diagnosis of patellar instability (Ridley et al, 2016;Prakash et al, 2016;Geraghty et al, 2022;Kim & Parikh, 2022). To date, in dogs, ROC analysis data on sensitivity, specificity, and cut-off values have been reported only for trochlear groove morphometric parameters in small and large breeds (Longo et al, 2023) and proximodistal patellar position indices (Murakami et al, 2023); however, there are no data on parameters of patellar morphology and patellofemoral alignment. This information seems valuable, as lameness affecting the opposite limb might have been missed in cases of bilateral MPL.…”
Section: Introductionmentioning
confidence: 99%